Exogenous factors impact on bacterial-microalgal growth and chromophoric dissolved organic matter: a case study of Chrysotila dentata and Marinobacter hydrocarbonoclasticus - Wang, Xueru; Sun, Jun (Frontiers in Marine Science, 2024)
The relationship between Chrysolia dentata and bacteria that play an important role in the carbon cycle is complex yet closely intertwined. However, there is still limited knowledge about how phytoplankton interacts with heterotrophic bacteria under external influences. Therefore, our investigation aimed to determine if introducing vitamin B12 and abscisic acid (ABA) would impact both growth and dissolved organic matter (DOM) release within a co-cultured environment consisting of Chrysotila dentata alongside Marinobacter hydrocarbonoclasticus (CA6). This experiment utilized artificial seawater (ASW) medium while employing three-dimensional (3D)-EEM for DOM analysis to quantify fluorescent peaks (B, T, A, and C) along with four indexes. Our findings indicate that the incubation of CA6 significantly enhances the release of protein-like components (peak T) and humic-like components (peak C) during the incubation period. However, 100 μg/L vitamin B12 (VB12) or abscisic acid does not promote axenic microalgae growth or release of C. dentata-derived DOM. However, they have different effects on C. dentata-CA6 growth and the derived DOM.Abscisic acid can facilitate steady growth of both C. dentata and CA6 cells while enhancing the amounts of humic-like components. Conversely, VB12 inhibits the growth of CA6 and results in a rapid decrease in protein-like signal, but it does not significantly enhance C. dentata growth or the transformation of DOM. This indicates that ABA can support stable co-grown of microalgal and bacteria in a water environment, while VB12 may hinder CA6 bacterial growth, resulting in a less stable co-cultured environment.